2006
DOI: 10.1002/cne.21103
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of synaptopodin and the spine apparatus organelle in the rat fascia dentata following entorhinal cortex lesion

Abstract: Synaptopodin is an actin-associated molecule essential for the formation of a spine apparatus in telencephalic spines. To study whether synaptopodin and the spine apparatus organelle are regulated under conditions of lesion-induced plasticity, synaptopodin and the spine apparatus were analyzed in granule cells of the rat fascia dentata following entorhinal denervation. Confocal microscopy was employed to quantify layer-specific changes in synaptopodin-immunoreactive puncta densities. Electron microscopy was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…These observations indicate that SP is associated with mature spines and that synaptic innervations may contribute to the targeting and maintenance of SP in dendritic spines. The results are consistent with studies which show lamina-specific alterations in the distribution of SP in the hippocampus after denervation (Deller et al, 2006) and after synaptic stimulation (Roth et al, 2001;Yamazaki et al, 2001;Fukazawa et al, 2003).…”
Section: Distribution Of Synaptopodin In Cultured Hippocampal Neuronssupporting
confidence: 92%
“…These observations indicate that SP is associated with mature spines and that synaptic innervations may contribute to the targeting and maintenance of SP in dendritic spines. The results are consistent with studies which show lamina-specific alterations in the distribution of SP in the hippocampus after denervation (Deller et al, 2006) and after synaptic stimulation (Roth et al, 2001;Yamazaki et al, 2001;Fukazawa et al, 2003).…”
Section: Distribution Of Synaptopodin In Cultured Hippocampal Neuronssupporting
confidence: 92%
“…Unlike dendritic arbors, dendritic spines are highly motile structures that have been shown to be swiftly and dynamically modulated by many factors such as changes in environment [29], gonadal hormones [27,28,30], physical compression and decompression [21,22], fatigue [20], insults such as axonal injury [31], deafferentation [32], and aging [33]. Here, we have shown that hyperammonemia significantly decreased the spine density in layer V sensorimotor cortical neurons (23-46%) and in hippocampal CA1 pyramidal neurons (24-47%).…”
Section: Discussionmentioning
confidence: 99%
“…1B). Considering that SP expression is altered under numerous pathological conditions (e.g., Reddy et al, 2005;Deller et al, 2006;Vlachos et al, 2008Vlachos et al, , 2013aStrehl et al, 2014), it is plausible that the ability of the ER to form these highly organized (SP-dependent) organelles might be of relevance in pathology.…”
Section: The Sa Controls Different Forms Of Synaptic Plasticitymentioning
confidence: 99%